Bedside tests to predict laryngoscopic difficulty in pediatric patients - Mansano, André Marques [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Silva, Leopoldo Muniz da [UNESP]; Ganem, Eliana Maria [UNESP]; Braz, Leandro Gobbo [UNESP]; Knabe, Andrea de Carvalho [UNESP]; Freitas, Fernanda Moreira de [UNESP] (Elsevier, 2016)
Background and Objectives: Pediatric airway management is a priority during anesthesia, critical care and emergency medicine. The purpose of this study is to validate bedside tests that predict airway management difficulty in anesthetized children. Methods: Children under 12 years of age were recruited in a cross-sectional study to assess the value of some anthropometric measures as predictors of laryngoscopic difficulty. The patients were divided into three groups by age. Weight, height, neck circumference, BMI (body mass index), inter incisors distance thyromental distance, sternomental distance, frontal plane to chin distance (FPCD) and the Mallampati index were determined and were correlated with the CML (Cormack & Lehane classification). Results: The incidence of difficult laryngoscopy (CML 3 or 4) was 3.58%. Factors that were significantly associated with laryngoscopic difficulty included short inter incisors distance, high FPCD, thyromental distance, sternomental distance and the Mallampati index. The FPCD/weight index exhibited a higher area under the ROC curve than any other variable considered. Conclusions: This study confirms that the FPCD and the FPCD/weight ratio are the most consistent predictors of laryngoscopic difficulty in pediatric patients. For patients over 6 months of age, the IID also correlated with laryngoscopic difficulty. For children who were capable of obeying simple orders, the Mallampati test correlated better with laryngoscopic difficulty than did the Mallampati test with phonation.Our results strongly suggest that skilled professionals should perform airway management in children, especially in patients with a high FPCD or a high FPCD/weight ratio.
Keywords: Anesthesia; Laryngoscopy; Pediatric; Predictors